2010
DOI: 10.3899/jrheum.091366
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Cognitive Impairment in Newly Diagnosed Systemic Lupus Erythematosus

Abstract: Depression, a modifiable risk factor, is associated with significantly poorer function in several cognitive domains in patients newly diagnosed with SLE. Treatment of depression when the CDS score is greater than 6 may improve cognitive functioning and should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 40 publications
(34 reference statements)
5
80
1
3
Order By: Relevance
“…Depression was improved by an approximate average of 9 points (post-intervention) and 5 points (four months post-intervention) on the BDI-II in intervention participants, which is greater than the minimum clinically significant change suggested for interpreting change scores in lupus trials[4244]. Overall, depression findings were consistent with other studies that have observed higher depression scores in SLE cases compared with controls[43, 45].…”
Section: Discussionsupporting
confidence: 83%
“…Depression was improved by an approximate average of 9 points (post-intervention) and 5 points (four months post-intervention) on the BDI-II in intervention participants, which is greater than the minimum clinically significant change suggested for interpreting change scores in lupus trials[4244]. Overall, depression findings were consistent with other studies that have observed higher depression scores in SLE cases compared with controls[43, 45].…”
Section: Discussionsupporting
confidence: 83%
“…47, p=0.07), functional relevance of NMNAT2 to SLE pathogenesis remains inconclusive and (4) although we observed correlation between SMG7 and SMG7-AS1 transcript levels, how SMG7 expression is regulated by its local lncRNA need further investigation.…”
Section: Discussionmentioning
confidence: 82%
“…As in human SLE where depression and other kinds of NP manifestations can appear early in the time course of the disease [15,89], authors found that depressive-like behavior is exhibited by MRL-lpr mice (stock #006825) already at 8-weeks of age, at a time when there was no other apparent organ involvement [90]. Thus, these mice demonstrate increased immobility in the forced-swim test, which is usually accepted as an indicator of depression in rodents if strength, motor coordination and general locomotion are otherwise normal (mice's motor function had been evaluated and revealed no impairment in the beam-walking as well as in open field tests).…”
Section: The Mrl-lpr Mouse Modelmentioning
confidence: 98%
“…NP manifestations seem not to be correlated with lupus flares [12], further confounding diagnosis and emphasizing the necessity to rule out other potential etiologies such as medication-induced (corticosteroid) psychiatric symptoms, infections, or metabolic abnormalities [13,14] to establish a possible diagnosis. While lupus patients with long duration of disease hold concurrently several factors that may provoke NP manifestations, affective, cognitive and mood disorders can be found in patients with newly diagnosed disease [15]. Disruption of blood brain barrier (BBB), brain pathology, and the presence of auto-antibodies (autoAbs) are central components of NPSLE.…”
Section: Introductionmentioning
confidence: 99%